Crosstalk between basal extracellular matrix adhesion and building of apical architecture during morphogenesis. - Barrera-Velázquez, M.; Ríos-Barrera, L.D. (Biology open, 2021)
Tissues build complex structures like lumens and microvilli to carry out their functions. Most of the mechanisms used to build these structures rely on cells remodelling their apical plasma membranes, which ultimately constitute the specialised compartments. In addition to apical remodelling, these shape changes also depend on the proper attachment of the basal plasma membrane to the extracellular matrix (ECM). The ECM provides cues to establish apicobasal polarity, and it also transduces forces that allow apical remodelling. However, physical crosstalk mechanisms between basal ECM attachment and the apical plasma membrane remain understudied, and the ones described so far are very diverse, which highlights the importance of identifying the general principles. Here, we review apicobasal crosstalk of two well-established models of membrane remodelling taking place during Drosophila melanogaster embryogenesis: amnioserosa cell shape oscillations during dorsal closure and subcellular tube formation in tracheal cells. We discuss how anchoring to the basal ECM affects apical architecture and the mechanisms that mediate these interactions. We analyse this knowledge under the scope of other morphogenetic processes and discuss what aspects of apicobasal crosstalk may represent widespread phenomena and which ones are used to build subsets of specialised compartments.